(untitled) (Communication Today, 2025)
Within the late modernity discourse attention has been drawn to the intensifying process of individualization. This process is being accelerated and affected by de-institutionalization and de-stratiﬁ cation – both processes resulting from the crisis of organised modernity. Individualization does not only mean more freedom and auto-nomy, it also implies more uncertainty and risk. In the liquid modernity people are facing a whole range of global uncertainty linked with crises of social forms, politics, social security, and conformity and consumer identity. All hopes and expectations towards the creating and accomplishing our life plans rest with us – individuals who are freer to take direction of their life trajectories, and at the same time, take responsibility for consequences of potential negative turbulences that could distract these trajectories from their settled direction. Being ﬂ exible is one of the most effective strategies how to tackle uncertainty in the age of liquid modernity. „Hunter-gamer“- a whole new concept of human mentality has been gaining more acceptance.